200 of 'Cassell's History of the War between France and Germany.... - The British Library (Wikimedia Commons, 2013)
Notice visuelle issue de Wikimedia Commons pour la demo du fonds documentaire.
Droits : Licence No known copyright restrictions via Wikimedia Commons
Keywords: Histoire; iconographie; gravure; photographie; Wikimedia Commons; Iconographie